SPECIATION AND ANTIBIOGRAM PATTERN OF TRIBE PROTEEAE WITH SPECIAL REFERENCE TO EXTENDED SPECRUM BETA LACTAMASE (ESBL) AND CARBAPENEMASE DETECTION - MEHARAJ, SH SHIFA; SHANMUGAM, PRIYADARSHINI; BANU AS, SHAMEEM (International Journal of Clinical and Biomedical Research, 2015)
Background:Proteusis a common uropathogen causing urinary tract infections in catheterised patients and those with urinary tract abnormalities. It may also lead to pyelonephritis, renal stones & bacteraemia. Multidrug resistant Proteeae isolates are major problem in treating nosocomial infections. Beta lactamase production is being increasingly demonstrated in most of the Proteus species. Apart from ESBL, Carbapenemase production is also emerging, thereby limiting the treatment options. Aim: To isolate, speciate and study the antibiotic resistance pattern of the Proteeae isolates. To identify the extended spectrum beta lactamase andcarbapenemase producing strains of Proteeae isolates by employing phenotypic methods. Materials and Methods: A total of 145 isolates of Proteus species isolated from different clinical samples- urine, pus and sputum, were included in this study. Antibiotic sensitivity testing was performed by Kirby-Bauer disk diffusion method. Screening tests for ESBL & Carbapenemase production was confirmed by Disk diffusion method and Modified Hodge test respectively. Results: Out of the 145 Proteeae isolates, from various clinical samples 70 were from wound swabs, 62 from urine, and 13 from respiratory specimens. The species were identified as 64 P.mirabilis, 48 P. vulgaris, 19 M. morganii, 5 Prov. stuartii and 9 Prov. rettgeri. Different antibiotic resistance patterns were observed in different species. Providencia species showed resistance to most of the antibiotics than the Proteus species and M morganii. Of the total, 52 (36%) were ESBL producers. Among the ESBL producers 6 (11.5%) were Carbapenamase producers. Conclusion: The increasing incidence of multi drug resistant strains in Tribe Proteeae has made antimicrobial susceptibility testing more important. Avoidance of indiscriminate use of antibiotics is the first step in prevention of newly emerging drug resistant strains. KEYWORDS: Proteeae; ESBL; Carbapenemase; Double disk Synergy test; Modified Hodge test.